The Influence of the Characteristics of Whistleblower to Whistleblowing Intentions - Venessa Angelin Yermia Djamal; Toto Warsoko Pikir; Rr. Puruwita Wardani (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2019)
Auditors have an important role both for companies and other parties who rely on audited financial information to make decisions. Cases involving the Public Accountant Firm (PAF) raise doubts about the auditor's performance. Therefore, efforts that can be made to increase that trust are by whistleblowing action, but it is not an easy action. The characteristics of whistleblower factors that influence a person's intention to conduct whistleblowing are attitudes toward behavior, subjective norms, perceptions of behavioral control, and commitment of professional. This study uses the Theory of Planned Behavior concept as a theoretical basis. The purpose of this study is to provide empirical evidence about the effect of attitudes toward behavior, subjective norms, perceptions of behavioral control, and the auditor's professional commitment to whistleblowing intentions. The study was conducted using primary data. The respondents in this study are an auditor who works in PAF in Surabaya. The sample in this study is 54 people with sampling techniques using convenience sampling. The analysis technique uses multiple linear regression analysis models. The results showed that attitudes toward behavior, subjective norms, and professional commitment were related to whistleblowing intentions, while perceived behavioral control did not conflict with whistleblowing intentions. This shows that auditors feel there will be difficulties and few opportunities in the process of disclosing known fraud, so that perceived behavioral control has no effect.